Association of Good Dairy Farming Practices, Welfare and Performance: A Review - Sorathiya, Lalitchandra Manjibhai (Indian Journal of Animal Production and Management, 2024)
This review underscores the critical role of good dairy farming practices in enhancing both animal welfare and dairy performance. International organizations like the World Organization for Animal Health (WOAH) and country-specific protocols emphasize the need for tailored Standard Operating Procedures (SOPs) to ensure effective and contextually appropriate practices. Advanced housing systems for calves, such as pair and group housing, have shown significant benefits in improving social interaction, cognitive development, and overall health. Effective pain management, particularly during procedures like disbudding, and optimized feeding strategies, including appropriate feed delivery timing and frequency, are crucial for enhancing health and productivity. Proper flooring, such as rubber mats, significantly improves cow comfort by providing a softer surface that reduces the risk of lameness and injuries associated with concrete floors. Effective pen management helps to mitigate dominance issues and minimize stress, leading to better welfare and productivity. Gentle handling practices, involving positive interactions like patting and stroking, significantly enhance animal welfare and milk production compared to aversive methods. Addressing issues such as mold and mycotoxins in feed is also essential for maintaining animal health and avoiding adverse effects on growth and milk production. Overall, adopting comprehensive dairy farming practices that prioritize animal welfare not only improves health and reduces stress but also leads to increased dairy productivity and sustainability, highlighting the interdependence of welfare and performance in the dairy industry.